Living on the Edge
476 p. 3 illus.
Keywords: In this volume, the European research project YUSEDER ("Youth Unemployment and Social Exclusion: Dimensions, Subjective Experiences and Institutional Responses in Six Countries of the EU"), supported by the EU Commission (Directorate General Research) as a part of the programme Targeted Socio-Economic Research (TSER), addresses the question of what effects long-term unemployment has on young people in regard of their feeling of belonging to society. Does long-term unemployment imply the risk of social exclusion for young people? How does social exclusion develop, and which factors counteract the processes of exclusion? Thus far, research into unemployment has seldom performed comparative studies. This interdisciplinary project in six European countries has conducted for the first time a qualitative study with 300 long-term unemployment young people from age 20 to 25. The inquiry was carried out in the three northern European countries Sweden, Belgium and Germany and in the three southern European countries Greece, Italy and Spain. Researches from psychology, sociology, public health and psychiatry participated in this research project coordinated by Thomas Kieselbach (University of Bremen, Germany). The volumes in the series published up to now within the YUSEDER project represent a state of the art overview of the topic of youth unemployment and health (volume 1) and youth unemployment and social exclusion (volume 2) in the six participating countries. This third volume focuses on the personal experiences and assessments of young people affected by unemployment. Besides presenting the country-specific manifestations of social exclusion, this new study identifies those important key mechanisms which increase (vulnerability factors) or reduce (protective factors) the risk of social exclusion. The results of this interdisciplinary comparative study represent an important basis for conceptualising future intervention measures in the European Union which could redu.